Modulation of amygdala response to task-irrelevant emotion. Issue 4 (24th January 2017) - Sebastian, Catherine L.; McCrory, Eamon J.; De Brito, Stephane A.; Viding, Essi
Abstract: It has been shown that as cognitive demands of a non-emotional task increase, amygdala response to task-irrelevant emotional stimuli is reduced. However, it remains unclear whether effects are due to altered task demands, or altered perceptual input associated with task demands. Here, we present fMRI data from 20 adult males during a novel cognitive conflict task in which the requirement to scan emotional information was necessary for task performance and held constant across levels of cognitive conflict. Response to fearful facial expressions was attenuated under high ( vs low) conflict conditions, as indexed by both slower reaction times and reduced right amygdala response. Psychophysiological interaction analysis showed that increased amygdala response to fear in the low conflict condition was accompanied by increased functional coupling with middle frontal gyrus, a prefrontal region previously associated with emotion regulation during cognitive task performance. These data suggest that amygdala response to emotion is modulated as a function of task demands, even when perceptual inputs are closely matched across load conditions. PPI data also show that, in particular emotional contexts, increased functional coupling of amygdala with prefrontal cortex can paradoxically occur when executive demands are lower.